THE ROLE OF MEDIA SOURCES IN THE FORMATION OF OPINIONS REGARDING THE ANTI-COVID-19 VACCINATION - RUSNAC Svetlana; CORDONEANU Elena (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The purpose of the research presented in this article was to measure the influence of information from the mass media on the decisions to vaccinate against COVID-19 of the citizens of the Republic of Moldova. The basic hypothesis assumed that the citizens of the Republic of Moldova who administered the anti-COVID-19 vaccine obtained information from official sources (TV, radio, online media channels, official information advertising, official information carriers, etc.). Citizens who did not get vaccinated against COVID-19, were influenced by speculative information, unofficially disseminated through social networks, fake news, did not contact officially argued sources and evidence, etc. The research group was made up of 100 people, taking into account age, sex, place of residence, level of education, marital and occupational status. In order to collect the experimental data, the survey method was used, applied through Google Forms. The research estimated the predictors of the willingness of citizens of the Republic of Moldova to get vaccinated against COVID-19: 1) trust in the official media, in government and medical institutions involved in the management of the pandemic crisis; 2) concern about the real danger caused by the SARS-Cov-2 virus; 3) the ability of medical institutions as bearers of official messages to debunk misinformation from the electronic media, especially from social networks. Age, gender, and area of residence are also significant predictors of availability for anti-COVID-19 vaccination: adults, men, and urban residents are more likely to receive the vaccine.